2018
DOI: 10.1097/md.0000000000012549
|View full text |Cite|
|
Sign up to set email alerts
|

Sarcomatous intrahepatic cholangiocarcinoma

Abstract: Rationale:Sarcomatous intrahepatic cholangiocarcinoma is a rare histological variant of cholangiocarcinoma (ICC). Previous medical literature has not mentioned the prevalence of this kind of disease, but a poorer prognosis than that of ordinary ICC was indicated. The diagnosis of the sarcomatous ICC is established on histopathological and immunohistochemical examinations. In this article, we present a new case of a patient with sarcomatous ICC who had no radiographic sign of intrahepatic tumor preoperatively.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…In published case reports, the median survival of patients with S-iCCA who underwent surgical resection was 11 months, which is comparable with that in patients with ordinary iCCA who did not undergo surgery (8 months). 4 The median survival of patients with S-iCCA who did AST: aspartate aminotransferase; ALT: alanine aminotransferase; GGT: gamma-glutamyl transferase; CEA: carcinoembryonic antigen; CA19-9: carbohydrate antigen 19-9; N/A: not available. not undergo surgery was 3 months, which is considerably shorter than that of patients with ordinary iCCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In published case reports, the median survival of patients with S-iCCA who underwent surgical resection was 11 months, which is comparable with that in patients with ordinary iCCA who did not undergo surgery (8 months). 4 The median survival of patients with S-iCCA who did AST: aspartate aminotransferase; ALT: alanine aminotransferase; GGT: gamma-glutamyl transferase; CEA: carcinoembryonic antigen; CA19-9: carbohydrate antigen 19-9; N/A: not available. not undergo surgery was 3 months, which is considerably shorter than that of patients with ordinary iCCA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that sarcomatoid hepatocellular carcinoma (HCC) may be associated with preoperative anticancer treatments, such as transcatheter arterial chemoembolization, radiofrequency ablation, or percutaneous ethanol injection. [4][5][6] However, there is no relevant study demonstrating the association between anticancer treatments and S-iCCA. Confirmation by biopsy and immunohistochemical staining is critical to establish a definitive diagnosis of S-iCCA.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, sarcomatous biliary carcinoma, including SIC and SCC, is very rare and malignant, which is diagnosed by postoperative histopathologic examinations. The prognoses of SIC and SCC were worse than that of ICC [22] and choledochal carcinoma. The pathologic diagnosis of metastasis of lymph nodes, and level of Ki-67 index of the tumor were possible indicators for postoperative survival.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] However, nearly all intrahepatic cholangiocarcinomas with spindle cell components are sarcomatous intrahepatic cholangiocarcinomas. [6][7][8][9] Accordingly, only a few reports have described carcinosarcomas, [10][11][12][13][14][15] and the characteristic spreading pattern and radiological findings of intrahepatic carcinosarcomas with cholangiocellular differentiation remain unclear.…”
Section: Introductionmentioning
confidence: 99%